Influence of carbon steel grade on the initial attachment of bacteria and microbiologically influenced corrosion. Issue 1 (2nd January 2016) - Javed, M.A.; Neil, W.C.; Stoddart, P.R.; Wade, S.A.
Abstract: The influence of the composition and microstructure of different carbon steel grades on the initial attachment (≤ 60 min) of Escherichia coli and subsequent longer term (28 days) corrosion was investigated. The initial bacterial attachment increased with time on all grades of carbon steel. However, the rate and magnitude of bacterial attachment varied on the different steel grades and was significantly less on the steels with a higher pearlite phase content. The observed variations in the number of bacterial cells attached across different steel grades were significantly reduced by applying a fixed potential to the steel samples. Longer term immersion studies showed similar levels of biofilm formation on the surface of the different grades of carbon steel. The measured corrosion rates were significantly higher in biotic conditions compared to abiotic conditions and were found to be positively correlated with the pearlite phase content of the different grades of carbon steel coupons.